Horacio Quiroga y el cuento fantástico - Olea Franco, Rafael (El Colegio de México, 2008)
This essay deals with the short story "El almohadón de pluma" (1907), in which Horacio Quiroga makes use of some of the conventions of the Gothic novel, but in a physical environment different from that usually chosen by English-speaking writers. The plot of the story postulates a typical fantastic universe. It depicts a world which is, at the beginning, familiar to and susceptible of being known by the characters but, later, these are confronted by an event that does not fit their realistic framework. The next-to-last paragraph, which is discursive and does not pertain to the development of the plot, explains the whole story and, thus, destroys its construction based on "indices". In the end, nevertheless, it would seem the story subtly threatens the reader with the category of "the strange".